Pengaruh Risiko Bisnis, Profitabilitas dan Pertumbuhan Aset terhadap Struktur Modal Perusahaan yang Terdaftar di Jakarta Islamic Index - Dela Khoiriyah; Rosyeni Rasyid (Universitas Negeri Padang, 2020)
Purpose - This study aims to determine the effect of business risk, profitability, and asset growth on the capital structure of companies listed on the Jakarta Islamic Index.Methodology - This research is classified as causative research. The population in this study were all companies listed on the Jakarta Islamic Index in 2014-2018. The sample in this study was determined by purposive sampling based on the criteria of companies listed in the Jakarta Islamic Index, companies that are consecutively ranked in the Jakarta Islamic Index during the 2014-2018. The samples in this study were 70. The type of data used is secondary data from the website www.idx.co.id. The analytical method used is multiple regression analysis using the SPSS program.Finding - The result of this study indicate (1) business risk has no significant negative effect on capital structure in companies listed on the Jakarta Islamic Index (2) profitability has a significant positive effect on capital structure in companies listed on the Jakarta Islamic Index (3) asset growth has a significant positive effect on capital structure in companies listed on the Jakarta Islamic Index